2009
DOI: 10.1016/j.juro.2008.10.146
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated H2AX in Noninvasive Low Grade Urothelial Carcinoma of the Bladder: Correlation With Tumor Recurrence

Abstract: Our data suggest that epigenetic alterations may have an important role in the mechanism of bladder tumor recurrence. Analysis in a larger cohort is needed to further assess our current preliminary findings of the role of gamma-H2AX expression for predicting outcome in low grade urothelial carcinoma cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Recently, we reported that global H3K4 and H3K20 methylation were decreased in BCa compared to normal urothelial tissue, and that global H4K20me3 levels were predictive for BCa-related death [7]. Low levels of histone H2AX phosphorylation at serine 139 have been identified as a risk factor for recurrence of NMIBC [9]; activation of the DNA damage response pathway results in H2AX phosphorylation and thereby recruits DNA repair effectors (e.g. BRCA1) [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that global H3K4 and H3K20 methylation were decreased in BCa compared to normal urothelial tissue, and that global H4K20me3 levels were predictive for BCa-related death [7]. Low levels of histone H2AX phosphorylation at serine 139 have been identified as a risk factor for recurrence of NMIBC [9]; activation of the DNA damage response pathway results in H2AX phosphorylation and thereby recruits DNA repair effectors (e.g. BRCA1) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Barbisan et al [8] reported in a small-scaled study decreased levels of H3K9Ac in recurrent papillary urothelial neoplasm of low malignant potential compared to non-recurrent papillary urothelial neoplasm of low malignant potential. Furthermore, phosphorylation of histone H2AX at serine 139 was correlated with a reduced risk of BCa recurrence following transurethral resection [9]. …”
Section: Introductionmentioning
confidence: 99%
“…66 In another study, gH2AX positivity was found to be associated with a lower rate of tumor recurrence in urothelial cancer patients, suggesting the prevention of accumulation of genomic damage. 67 In addition, Toyoda et al 68 suggested that gH2AX may be a potential biomarker for the early detection of genotoxic bladder carcinogens. In another study, gH2AX was found to play a role in the differentiation status of thyroid cancer.…”
Section: Gh2ax Studies: Biosamplingmentioning
confidence: 99%
“…Mesane tümöründe histon modifikasyonlarının prognostik değerine bakıldığında, düşük malign potansiyelli papiller ürotelyal neoplazmda azalmış H3K9ac seviyesi artmış rekürrens eğilimi ile ilişkili olarak bulunmuştur (54). Bunun aksine, histon H2AX'ın (H2AXS139Ph) serin 139'unun fosforilasyonu transüretral rezeksiyon (TUR) sonrası düşük rekürrens riski ile ilişkilidir (55). Farklı evrelerdeki mesane tümörlü hastaların dokularının incelendiği yakın zamandaki bir çalışma H3K4me1, H4K20me1, H4K20me2 ve H4K20me3 immünekspresyon düzeylerinin ileri patolojik evre ile korele olduğunu; H4K20me3'ün kas invaziv mesane tümörlü hastalarda hastalığa spesifik sağkalımın bağımsız prognostik prediktörü olduğu gösterilmiştir (56).…”
Section: Epigenetik Belirteçlerin Prognostik öNemiunclassified